PERAN GURU QUR’AN HADITS DALAM MENINGKATKAN KUALITAS BACAAN METODE BIL QOLAM SISWA - Inayatul Fadila; Kukuh Santoso; Bagus Cahyanto (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to determine the teacher's role in improving the quality of reading the Qur'an using the Bil Qolam method of students in MTs. Irsyadul Mubtadi'in Singosari. This research uses a descriptive qualitative approach with the type of case study research. The data collection procedure used observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. Planning the teacher's role in improving the reading quality of students using the Bil Qolam method, namely the teacher acts as a teacher, mentor and motivator. Learning using the Bil Qolam method is carried out before the lesson begins with an allocation of 60 minutes. The teacher carries out a learning strategy by introducing letters, makharijul hurf, and tajwid rules. The benchmark for student success is that students are able to read the Qur'an properly and correctly, do not falter in reading the Qur'an and in accordance with their tajwid and makhraj, so that students are said to be capable of reading the Qur'an.